2004
DOI: 10.1097/01.ede.0000142150.60556.b8
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon and Lung Cancer in France

Abstract: Our results support the presence of a small excess lung cancer risk associated with indoor radon exposure after precise adjustment on smoking. They are in agreement with results from some other indoor radon case-control studies and with extrapolations from studies of underground miners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…This result was entirely unexpected. There have been many other reports in case-control studies of ORs below one in the low dose region but in all cases without statistical significance (Blot et al 1990;Letourneau et al 1994;Alavanja et al 1994Alavanja et al , 1999Auvinen et al 1996;Kreuzer et al 2003;Baysson et al 2004;Wichmann et al 2005;Sandler et al 2006). What reasons can be offered for this difference?…”
Section: Discussionmentioning
confidence: 99%
“…This result was entirely unexpected. There have been many other reports in case-control studies of ORs below one in the low dose region but in all cases without statistical significance (Blot et al 1990;Letourneau et al 1994;Alavanja et al 1994Alavanja et al , 1999Auvinen et al 1996;Kreuzer et al 2003;Baysson et al 2004;Wichmann et al 2005;Sandler et al 2006). What reasons can be offered for this difference?…”
Section: Discussionmentioning
confidence: 99%
“…Among them, most were excluded after abstract because they were occupational studies on miners, no case control studies, no relevant exposure or endpoint, and reviews. After assessing the full-text of the 38 relevant articles, we identified 22 eligible studies for meta-analysis (Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al,1992Pershagen et al, , 1994Alavanja et al, 1994Alavanja et al, , 1999Létourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Field et al, 2000;Sobue et al, 2000;Lagarde et al, 2001;Pisa et al, 2001;Barros-Dios et al, 2002;Wang et al, 2002;Baysson et al, 2004;Bochicchio et al, 2005;Wichmann et al, 2005;Sandler et al, 2006;Thompson et al, 2008;Wilcox et al, 2008). Seven studies were excluded for previous mete-analysis (Lubin and Boice, 1997;Pavia et al, 2003) and combined analysis in Europe, North America or China Darby et al, 2005;Krewski et al, 2005;Wang et al, 2005;Darby et al, 2006).…”
Section: Literature Searchmentioning
confidence: 99%
“…The number of control ranged from 35 to 4232, with a sum of 21102. Of the included studies, the majority was populationbase control, whereas three were hospital-based control (Baysson et al, 2004;Bochicchio et al, 2005;Thompson et al, 2008) and one combined population and hospital subjects as control (Darby et al, 1998). Half studies ascertained lung cancers from national/local cancer registries and the other half from hospitals.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies showed a negative ERR (Blot et al 1990;Letourneau et al 1994;Kreienbrock et al 2001). In a report on indoor radon and lung cancer in France, Baysson et al (2004) claimed a small ERR. The data was compatible with a decreasing risk rather than an increasing risk (Lachet 2005).…”
Section: Radon Exposure and Relative Riskmentioning
confidence: 99%